Pendampingan Guru Madrasah untuk Mewujudkan Kompetensi Pedagogik Guru Matematika yang Berdaya Melalui Penguasaan Soal High Order Thinking Skills (HOTS) - Moh Hafiyusholeh; Ahmad Lubab; Ahmad Hanif Asyhar; Aris Fanani; Yuniar Farida; Dian C. Rini Novitasari; Nurissaidah Ulinnuha; Putroue Keumala Intan; Wika Dianita Utami; Zainullah Zuhri; Ahmad Zaenal Arifin; Dian Yuliati; Abdulloh Hamid (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
High Order Thinking Skills (HOTS) is the ability to connect, manipulate, and change the knowledge and experience that is owned critically and creatively in determining decisions to solve problems in new situations. To include HOTS questions in a learning process is an obstacle for Madrasah teachers, including teachers of PC. LP. Maarif NU Lamongan. This community service aimed at improving the pedagogical competence of mathematics teachers of PC. LP. Maarif NU Lamongan. Community-Based Research (CBR) was employed through workshop and training administered by the Mathematics Study Program of UIN Sunan Ampel Surabaya in designing and completing high order thinking questions followed by assistance. The results indicated that the ability of Madrasah teachers to solve HOTS questions as well as its implementation in classroom teaching and learning activities improved significantly.